Total carotenoids and antioxidant characteristics of cassave (Manihot asculenta Crantz) lakan-1 and golden yellow varieties. ? - Lirazan, Jazer John T.
Cassava is a resilient plant that provides good production yield all year. It serves as a good reservoir and nutrient source in the different regions of the world. Cassava contains carotenoids which has several health benefits, one of which is its antioxidant property. The study provides a good baseline data for both qualitative and quantitative analysis of the total carotenoid content of Lakan-1 and Golden Yellow varieties. The total carotenoid content of two cassava varieties measured using UV-Vis spectrometer against carrots carotenoids were found to be 2.78±0.00% for Golden Yellow and 1.29±0.00% for Lakan-1. The FTIR spectra show high similarity of the absorption bands and prominent peaks of the carrots standard, the Lakan-1 and Golden Yellow cassava carotenoids. Similar peaks were also observed at wavenumbers 1460-1465 cm^(-1) and 1730-1740cm^(-1). This shows the possible presence of carotenoids in the cassava samples. The carotenoids in both samples show good antioxidant property of 58.79% and 64.40% inhibition for Lakan-1 and Golden Yellow varieties, respectively at 500 ppm. The IC_50 is 2.29 ppm and 2.26 ppm for Lakan-1 and Golden Yellow varieties, respectively.